THE EFFECT OF EMOTIONAL INTELLIGENCE AND LEARNING BEHAVIOR ON THE LEVEL OF ACCOUNTING UNDERSTANDING ON ACCOUNTING STUDENTS FEB UMSU - Retno Widia Ningsih; Hafsah Hafsah (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study was to test and analyze the effect of emotional intelligence on the level of accounting understanding, to test and analyze student learning behavior on the level of accounting understanding and to test and analyze the effect of emotional intelligence and student learning behavior on the level of accounting understanding. The analytical technique used in this study is quantitative data analysis, namely testing and analyzing data through online questionnaires to respondents. The research population is 371 students with a target sample of 175 people and those who return questionnaires so that 55 people become permanent respondents. The analysis used is multiple linear regression. The results of the study partially prove that Emotional Intelligence has no effect on the level of understanding of accounting in FEB UMSU students, the results partially prove that student learning behavior affects the level of understanding of accounting in students of FEB UMSU. Emotional Intelligence and Student Learning Behavior have an effect on Level of Accounting Understanding for FEB UMSU Students.